Determinants of Electronic Payment System Use in the Kathmandu Valley: A Structural Equation Modeling Approach Integrating TAM and TPB (Quest Journal of Management and Social Sciences, 2025)
Background: The growing digitalization of financial transactions, driven by rising internet penetration in Nepal, has accelerated the adoption of electronic payment systems. However, understanding the determinants influencing users' behavioral intentions remains critical for sustainable growth.Purpose: This study aims to examine the key factors shaping customers' perceptions and adoption of e-payment systems in the Kathmandu Valley by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) within a unified analytical framework.Design/methodology/approach: An explanatory research design was employed, collecting data from 433 customers of commercial banks in the Kathmandu Valley through convenience sampling. Both descriptive and inferential analyses were performed, while Structural Equation Modeling (SEM) was utilized to evaluate the relationships among variables derived from TAM and TPB constructs.Results: The findings reveal that awareness of e-payment systems is high, primarily driven by exposure to social media. Most respondents actively use e-wallets and online gateways for bill payments and mobile transactions. Nevertheless, security concerns remain a major barrier, significantly affecting users' trust and satisfaction. The constructs of perceived usefulness, ease of use, and customer satisfaction emerged as strong predictors of behavioral intention toward e-payment usage.Conclusion: The study highlights the need to enhance system security, simplify user interfaces, and reinforce trust-building mechanisms. Service providers and policymakers should prioritize security improvements, promote awareness of benefits, and continuously refine digital payment platforms in response to user feedback and technological advancements.Keywords: Electronic payment, technology acceptance model, theory of planned behavior, structural equation modeling, behavioral intention, Kathmandu Valley